Ferramentas experimentais e teóricas aplicadas em elucidação de reações orgânicas - Leonarczyk, Ives Antonio (2019)
EXPERIMENTAL AND THEORETICAL TOOLS APPLIED FOR ORGANIC REACTIONS ELUCIDATION. The present thesis explore different problems involving organic reactions using the association between experimental methodologies and theoretical calculations based in DFT. The first work has shown unprecedented evidence suggesting mechanistic differences afford by the type of catalyst employed in the A3 multicomponent synthesis of 2,4-diphenylquinolines. Thus, using iron salts or montmorillonite is favorable the Povarov-type mechanism, not have been observed the propargylamine intermediate proposed by literature. The second work investigates the remote sense of 1,4 and 1,5 asymmetric induction in boron mediate aldolic reactions using -alkoxy and -bis-alkoxy methyl ketones. In this inedited study, was systematically analyzed as well the role of -alquil substituents as the stereoelectronic influence of different oxygen protecting groups in  and positions for the process. DFT calculations have shown the source of 1,4-selectivity in terms of -substituent as well the synergistic effects between the -syn and -anti-bis-alkoxy stereocenter was elucidated leading to rationalize a new model. Thus, in case of 1,5-stereoinduction in presence of -alkoxy center the reaction follows the analogous Goodman-Paton model. The last work, disclose about the combined use of different computational methods aiming conformational analysis and NMR parameters calculations ( and 3J) for aldol adducts -branched and -unbranched where the conformational flexibility shows an elucidation challenge through direct methods. The results shown a more complex conformational scenario than the current accepted by literature, where different hydrogen bonds compete for stabilize the structures in equilibrium, revealing the possible origins observed in NMR parameters, where new considerations were presented to literature model.